Evaluasi Kebijakan Pendidikan Dalam Meningkatkan Mutu Lembaga Pendidikan - Marsyela M; Marsyeli M; Tasya Widyana; Dita Oktaviani; Tengku Darmansah (Madani: Jurnal Ilmiah Multidisiplin, 2025)
Education is the main pillar in creating quality human resources. Education policy has a strategic role in ensuring the achievement of optimal educational goals. However, the implementation of these policies often faces various challenges, especially in improving the quality of educational institutions in schools. This research aims to evaluate educational policies that have been implemented to improve the quality of education in schools. The method used is a qualitative approach with data analysis through in-depth study of literature from various journal and book references. The research results show that education policies that focus on increasing teacher competency have a positive impact on the quality of learning. Apart from that, this article explains the meaning of education policy, the quality of education, the objectives of evaluating education policy, as well as strategies for improving the quality of education. Therefore, synergy is needed between the government, schools and society to improve the overall quality of education.